Digital Literacy and Islamic Values: Strengthening Religious Understanding in The Era of AI-Based Learning - Mohammad Fauzan; Nur Amalina; Muhamad Ismail (Global Perspectives in Education Journal, 2026)
This study aims to examine the relationship between students’ digital literacy and their understanding of Islamic values in the context of AI-based learning at SMK Farmatikom Pekanbaru. Conducted in August 2025 with 121 student respondents, the research explores how digital competencies influence religious comprehension as learning environments increasingly integrate artificial intelligence. A quantitative approach was employed using a correlational survey design. Digital literacy and understanding of Islamic values were measured using validated Likert-scale instruments, and the data were analyzed through descriptive statistics, Pearson correlation, and multiple regression techniques. The results indicate that students’ digital literacy levels fell into the medium-to-high category, and a significant positive correlation was found between digital literacy and understanding of Islamic values. Multiple regression analysis further revealed that digital literacy significantly predicted students' understanding of religion within AI-supported learning platforms. These findings suggest that strengthening digital literacy can enhance students’ ability to interpret, evaluate, and apply Islamic values in technologically advanced learning environments. The study highlights the importance of integrating value-based digital education to support both cognitive and moral development among vocational high school students.